Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/10668926.2013.850758
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Among Community College Students: Prevalence and Association With Grade Point Average

Abstract: This study investigated the prevalence of food insecurity among community college students (N = 301) and the relationship between food insecurity and student grade point average (GPA). It employed a cross-sectional intercept survey, utilizing the U.S. Department of Agriculture's Household Food Security Survey Module, student self-reported GPA, and demographic variables. The research setting was two community colleges in Maryland-one located in a low income urban area and one located in an affluent suburban are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
189
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(208 citation statements)
references
References 16 publications
16
189
3
Order By: Relevance
“…Basic needs insecurity compromises community college students’ performance in school (Broton, ; Maroto, Snelling, & Linck, ), negatively impacting their grades and chances of persisting and graduating. Students who experience basic needs insecurity report higher rates of missing classes and study sessions, opting out of extracurricular activities, not buying required books, and dropping classes due to hunger and housing problems (Mercado, ).…”
Section: Evidence Of a Crisismentioning
confidence: 99%
“…Basic needs insecurity compromises community college students’ performance in school (Broton, ; Maroto, Snelling, & Linck, ), negatively impacting their grades and chances of persisting and graduating. Students who experience basic needs insecurity report higher rates of missing classes and study sessions, opting out of extracurricular activities, not buying required books, and dropping classes due to hunger and housing problems (Mercado, ).…”
Section: Evidence Of a Crisismentioning
confidence: 99%
“…There are physical and psychological consequences associated with food and housing insecurity (Evans, Wells, and Moch, 2003;GoldrickRab, Broton, and Eisenberg, 2015;Melchior et al, 2009), which might harm academic performance. For example, Maroto, Snelling, and Linck (2015) found that food insecurity is associated with lower grade point averages (GPAs) among community college students. A 2010 survey of City University of New York (CUNY) students found that more than two in five reported housing-insecurity issues, including not having enough money to pay rent and being evicted .…”
Section: The Importance Of Effective College Support Programs the Rolmentioning
confidence: 99%
“…The negative deficiencies (inattention, distractibility, fatigue) associated with inadequate nutrition have been known in K‐12 students since the 1970s (Alaimo, Frongillo, & Olson, ). Among community college students, food insecurity has also been shown to be related to poorer academic performance (Maroto, Snelling, & Linck, ). Some educators have attempted to alleviate food insecurity through the provision of campus‐based food banks or food pantries (Twill, Bergdahl, & Fensler, ; Dubick, Mathews, & Cady, ).…”
Section: Food Insecurity From the Higher Education Perspectivementioning
confidence: 99%